Characterization of electrospun nanofibers and solvent-casted films based on Centaurea arvensis anthocyanin-loaded PVA/κ-carrageenan and comparing their performance as colorimetric pH indicator. (15th September 2022) - Forghani, Samira; Zeynali, Fariba; Almasi, Hadi; Hamishehkar, Hamed
Graphical abstract: Highlights: Centaurea arvensis anthocyanin (CAE) was introduced as a colorimetric pH indicator. PVA/Ҡ-carrageenan mixtures were used for immobilization of CAE. Electrospun nanofibers and solvent casted films were compared as pH indicators. The indicators showed a distinct color change over the pH range of 2–12. The color change response of electrospun nanofibers was higher than films. Abstract: In this research, PVA/Ҡ-carrageenan-based colorimetric indicators incorporated with Centaurea arvensis anthocyanin (CAE) were fabricated by two electrospinning and solvent casting methods and their performance as pH indicators were assessed. Chemical immobilization of CAE on PVA and PVA/Ҡ-carrageenan matrixes was approved by FT-IR analysis. According to SEM images, Ҡ-carrageenan addition improved the homogeneity of films and decreased the diameter of nanofibers. The crystalline structure and thermal properties of polymeric matrixes were affected by anthocyanin incorporation. CAE had an adverse effect on mechanical properties of films and nanofibers. The preparation method and type of solid matrix affected the responsiveness and the tonality of responded color. Electrospun nanofibers showed high responsiveness (10 s) than colorimetric films (15–40 min) to pH changes. The indicators displayed color variations from heather violet to green over the 2–12 pH range. The designed indicators have potential to be applied as visual pH label in food intelligent packaging.